MANIFESTO POR UM CURRÍCULO-CORAJOSO NA EDUCAÇÃO DAS INFÂNCIAS - Gurgel, Evanilson (Literatura em Debate, 2025)
This article, written in the form of a manifesto, addresses the challenges of being a teacher in a time and space that offers such unflattering images of the teaching profession, especially when we dare to translate our pedagogical practice into curriculum that embrace differences and minorities. Therefore, the purpose of the text is to discuss the principles of a courageous curriculum, an artifact whose vitality is a driving force for dealing with the various strategies used to suppress our classroom practices, particularly in Early Childhood Education. My starting point is an episode with children during my time in Early Childhood Education, which sparked a reflection on the need to embody courage in times of incessant production of anxiety and fear in our teaching. I conclude with some notes on the creation of a courageous curriculum, capable of provoking small tremors in the everyday microfascisms through creative resistance, fueled by dreams, which allows life to endure.